PENGARUH TAX PLANNING DAN TAX RISK ASSESSMENT TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PENGETAHUAN PAJAK SEBAGAI MODERASI - Sitorus, Riris Rotua; Humairo, Mutiara (Media Akuntansi Perpajakan, 2019)
This research was conducted with the aim to study the effect of tax planning and tax risk assessment on compliance taxpayers with tax knowledge as moderation. The method used is a measurement method by distributing questionnaires and doing calculations using Smart PLS.The results of the study show that tax planning and tax knowledge have a positive and significant effect while tax risk assessment, tax planning with tax knowledge as a moderator and tax risk assessment with taxpayer knowledge as a moderator has no influenceKeywords : Tax Risk Assessment, Tax Planning, Compliance, Knowledgement, Tax Payer